Current status of space gravitational wave antenna DECIGO and B-DECIGO. (22nd February 2021) - Kawamura, Seiji; Ando, Masaki; Seto, Naoki; Sato, Shuichi; Musha, Mitsuru; Kawano, Isao; Yokoyama, Jun'ichi; Tanaka, Takahiro; Ioka, Kunihito; Akutsu, Tomotada; Takashima, Takeshi; Agatsuma, Kazuhiro; et al.
Abstract: The Deci-hertz Interferometer Gravitational Wave Observatory (DECIGO) is a future Japanese space mission with a frequency band of 0.1 Hz to 10 Hz. DECIGO aims at the detection of primordial gravitational waves, which could have been produced during the inflationary period right after the birth of the Universe. There are many other scientific objectives of DECIGO, including the direct measurement of the acceleration of the expansion of the Universe, and reliable and accurate predictions of the timing and locations of neutron star/black hole binary coalescences. DECIGO consists of four clusters of observatories placed in heliocentric orbit. Each cluster consists of three spacecraft, which form three Fabry–Pérot Michelson interferometers with an arm length of 1000 km. Three DECIGO clusters will be placed far from each other, and the fourth will be placed in the same position as one of the other three to obtain correlation signals for the detection of primordial gravitational waves. We plan to launch B-DECIGO, which is a scientific pathfinder for DECIGO, before DECIGO in the 2030s to demonstrate the technologies required for DECIGO, as well as to obtain fruitful scientific results to further expand multi-messenger astronomy.